2002
DOI: 10.1901/jaba.2002.35-403
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Children's Behavior to Probabilistic Reward: Effects of a Decreasing‐ratio Lottery System on Math Performance

Abstract: Probabilistic reward has been shown to affect children's choice behavior in game-like activities. We examined the effects of a lottery system containing progressively lower exchange ratios on children's completion of math problems. Two of the 3 children completed problems above baseline levels until the chance of exchange dropped to 25%. This study describes a potentially useful method for examining reinforcement schedules in applied settings and extends previous research on probabilities of reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Despite these limitations, results of the present study are consistent with previous research showing that children may exhibit risk‐prone behavior under some conditions (e.g., Cuvo, Lerch, Leurquin, Gaffaney, & Poppen, ; Martens et al, ). For example, Martens et al gave children the opportunity to complete difficult math problems, exchange completed difficult problems for slips of easy problems, and then exchange completed easy problem slips for back‐up reinforcers using a chain schedule.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these limitations, results of the present study are consistent with previous research showing that children may exhibit risk‐prone behavior under some conditions (e.g., Cuvo, Lerch, Leurquin, Gaffaney, & Poppen, ; Martens et al, ). For example, Martens et al gave children the opportunity to complete difficult math problems, exchange completed difficult problems for slips of easy problems, and then exchange completed easy problem slips for back‐up reinforcers using a chain schedule.…”
Section: Discussionsupporting
confidence: 91%
“…That is, children may still prefer to complete academic work rather than obtain reinforcement freely even as the schedule of reinforcement is thinned (Dave and Tim preferred CR at FR values of 7 and 9, respectively). Observing preference for CR in an instructional context under INT reinforcement provides some evidence that thinning the reinforcement schedule following the acquisition of an academic response (Baer et al, 1987; Cooper et al, 2007; Martens et al, 2002; McGinnis et al, 1999) can still result in a preferred learning context.…”
Section: Discussionmentioning
confidence: 99%
“…A common goal in practice is to thin the schedule of reinforcement to increase the practicality for caregivers and teachers. Given the prevalence of intermittent (INT) reinforcement in clinical and educational contexts (Baer, Blount, Detrich, & Stokes, 1987; Cooper, Heron, & Heward, 2007; Martens et al, 2002; McGinnis, Friman, & Carlyon, 1999), evaluating whether preference for CR persists as the schedule of reinforcement is thinned warrants investigation.…”
mentioning
confidence: 99%
“…For example, 1 study showed that only the lowest incentive condition (25%, as opposed to 50%, 75%, and 100%) was ineffective in improving 3 female elementary school students’ performance in solving math problems. 35 Another study reported that a 3% condition resulted in the lowest job performance of 2 teaching assistants compared to 6%, 12%, and 25% conditions. 28 However, other studies have reported that the effect of the chance of winning the lottery is minimal.…”
Section: What Are Your Research’s Implications Towards Theory Practic...mentioning
confidence: 98%